Characterization of the Full-Length Genome Sequences and Phylogenetic Analysis of HDV Strains Isolated from Patients with Chronic HBV and HDV Infection in Kyrgyz Republic - Yu. V. Ostankova; K. A. Nogoybaeva; E. B. Zueva; K. T. Kasymbekova; S. T. Tobokalova; A. V. Semenov (Проблемы особо опасных инфекций, 2020)
Objective. The purpose of our work was molecular genetic characterization of the hepatitis D virus isolates, circulating in the region with high prevalence of HBV + HDV super-infection. Materials and methods. The study material was 64 blood serum samples obtained from Kyrgyz Republic residents - patients with chronic viral hepatitis B+D. The hepatitis D virus complete genomes were sequenced, followed by phylogenetic analysis. Results and discussion. Based on the phylogenetic analysis of 64 HDV samples, it was shown that HDV genotype 1 (96.9 %) predominates in the examined group compared with HDV genotype 2 (3.1 %). Sequences were submitted to GenBank under access No MN984407 through MN984470. When assessing the genetic variability over the examined HDV genotype 1 samples, the maximum genetic distance was 12,49 %, and the minimum – 7,41 %. Within individual clusters, the genetic distance averaged from 2.6 % to 8.5 %. Among the sequences in GenBank, the closest resemblance to the HDV-2 Kyr41 and Kyr43 samples (nucleotide identity was 92.31 % and 89.57 %, respectively) was shown for the virus described earlier in Yakutia (AJ309880). To study the genetic relationships between the analyzed HDV genotype 1 strains in comparison with the HDV reference sequences, the predicted amino acid sequence was studied (111–214). Although hepatitis B preventive measures, including vaccination, have reduced the hepatitis D incidence, there is no effective way to prevent HDV infection in HBV carriers in endemic areas. The HDV sequence molecular-genetic characterization in this study, as well as the viral genomic sequence phylogenetic analysis, will help identify pathogen transmission pathways to control and / or prevent the spread of infection.